Detection of hyperphosphorylated tau protein and α-synuclein in spinal cord of patients with Alzheimer’s disease - Guo Y; Wang L; Zhu M; Zhang H; Hu Y; Han Z; Liu J; Zhao W; Wang D (Neuropsychiatric Disease and Treatment, 2016)
Yanjun Guo,1,2 Luning Wang,2 Mingwei Zhu,2 Honghong Zhang,3 Yazhuo Hu,3 Zhitao Han,3 Jia Liu,4 Weiqin Zhao,1 Dexin Wang11Department of Neurology, Beijing Friendship Hospital, Capital Medical University, 2Department of Geriatric Neurology, PLA General Hospital, 3Institute of Geriatrics, Chinese PLA General Hospital & Chinese PLA Medical Academy, 4Department of Neurology, Xuanwu Hospital, Capital Medical University, Beijing, People’s Republic of ChinaAbstract: The aim of this study was to investigate the neuropathological features of the spinal cord in patients suffering with Alzheimer’s disease (AD). Spinal cord tissue collected from three AD patients and eight controls was selected for the study. Data were collected at T2, T8, T10, L4, and S2 spinal levels. The sections were subjected to hematoxylin and eosin and Gallyas–Braak staining methods and then were immunostained with antibodies such as phosphorylated tau protein (AT8), α-synuclein, Aβ, amyloid precursor protein , ubiquitin, and TDP-43. Pathological changes exhibited by the biomarkers were detected by microscopy. Neurofibrillary tangles (NFTs) were detectable in spinal anterior horn motor neurons in two of the three AD patients. AT8-positive axons or axon-like structures and AT8 expression in glial cells were detected in all three AD cases. Hyperphosphorylation of tau protein was detected in spinal anterior horn cells, glial cells, and axons, and its severity was associated with NFTs in the brain tissue. α-Synuclein-positive Lewy bodies and scattered Lewy-like neuritis were detected in the medial horn of the thoracic spinal cord and ventral sacral gray matter, respectively, in one patient who had AD with Lewy bodies. Neither amyloid deposition nor amyloid precursor protein and TDP-43 expression was detected in the spinal cord of AD patients. Spinal cord of AD patients was observed to contain phosphorylated tau protein and α-synuclein immunoreactive structures, which may play a role in dyskinesia and autonomic dysfunction in advanced AD.Keywords: Alzheimer’s disease, α-synuclein, tau protein, neurofibrillary tangles, histopathology